2023
DOI: 10.1093/cercor/bhad004
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient speech-motor control affects predictive speech comprehension: atypical electrophysiological correlates in stuttering

Abstract: Listeners predict upcoming information during language comprehension. However, how this ability is implemented is still largely unknown. Here, we tested the hypothesis proposing that language production mechanisms have a role in prediction. We studied 2 electroencephalographic correlates of predictability during speech comprehension—pre-target alpha–beta (8–30 Hz) power decrease and the post-target N400 event-related potential effect—in a population with impaired speech-motor control, i.e. adults who stutter (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 135 publications
1
18
0
Order By: Relevance
“…For naming latencies (response times, RT), we took the data from (Gastaldon et al, 2023), also available here: https://osf.io/5jkur/. Here we summarize how latencies were derived in the original study, but we refer the reader to the original article for additional details.…”
Section: Naming Accuracy and Response Times Analysis (Listening-for-s...mentioning
confidence: 99%
See 1 more Smart Citation
“…For naming latencies (response times, RT), we took the data from (Gastaldon et al, 2023), also available here: https://osf.io/5jkur/. Here we summarize how latencies were derived in the original study, but we refer the reader to the original article for additional details.…”
Section: Naming Accuracy and Response Times Analysis (Listening-for-s...mentioning
confidence: 99%
“…For both listening conditions, sentences could either be highly or low constraining towards a specific word completing the sentence. In this study, in order to allow for a better estimation of CTS and increase statistical power, we have not divided the unfinished sentence into high vs low constraining as in the original study (Gastaldon et al, 2023). Instead, we focused on the manipulation of the task, which implied two different listening conditions: listen with the aim of comprehending and answer to a true/false judgment question that appeared on the screen in the 20% of the trials (listening only), and listen in order to be ready to complete the sentence as quickly as possible by naming a picture (listening-for-speaking).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…However, precision levels fluctuate spontaneously during the task even in presence of equally reliable cues (Feldman & Friston, 2010) and there is evidence that higher precision levels are associated with lower pre-stimulus power (Bauer et al, 2014;Cao et al, 2017). In Section 1.1, we reviewed evidence stating that in sentence comprehension paradigms featuring different levels of contextual constraint, more constraining contexts were associated with lower levels of pre-stimulus alpha power (Gastaldon et al, 2020;León-Cabrera et al, 2022;Rommers et al, 2017;Terporten et al, 2019;Wang et al, 2018), while similar studies found that contexts eliciting lower pre-stimulus alpha power were associated with more negative N400s (Gastaldon et al, 2023;Rommers et al, 2017;Terporten et al, 2019;Wang et al, 2018). This body of evidence helped us generate the hypothesis that lower pre-stimulus alpha might be associated with more precise predictions.…”
Section: Precision and Attentionmentioning
confidence: 99%
“…Additional supporting information can be found online in the Supporting Information section at the end of this article. Data S1: Supporting Information How to cite this article: Lago, S., Pezzetta, R., Gastaldon, S., Peressotti, F., & Arcara, G. (2023). Trial-by-trial fluctuations of pre-stimulus alpha power predict language ERPs.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation